2008
DOI: 10.3892/ijo.33.1.175
|View full text |Cite
|
Sign up to set email alerts
|

siRNA targeting the IRF2 transcription factor inhibits leukaemic cell growth

Abstract: Abstract. Interferon regulatory factor (IRF) 1 and its functional antagonist IRF2 were originally discovered as transcription factors that regulate the interferon-ß gene. Control of cell growth has led to the definition of IRF1 as a tumour suppressor gene and IRF2 as an oncogene. Clinically, approximately 70% of cases of acute myeloid leukaemia demonstrate dysregulated expression of IRF1 and/or IRF2. Our previous studies have shown that human leukaemic TF-1 cells exhibit abnormally high expression of both IRF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Waf1 tumor suppressor effects (11). The IRF-2BP2 knockdown data from U2OS cells seem to support this model (35).…”
Section: Discussionmentioning
confidence: 90%
“…Waf1 tumor suppressor effects (11). The IRF-2BP2 knockdown data from U2OS cells seem to support this model (35).…”
Section: Discussionmentioning
confidence: 90%
“…In diverse types of cancers, the expression of IRF-2 was found to positively associate with the malignant phenotype and be critical for the tumorigenicity of cancer cells [20,24,26]. Previous studies indicated that IRF-2 exerts it oncogenic activity in ESCC by affecting expression of certain genes involved in cell proliferation and apoptosis [25,26].…”
Section: Discussionmentioning
confidence: 97%
“…Recently, more and more evidence uncovered the pivotal role of IRF-2 in tumor progression [18,19]. By suppressing the function of p21, IRF-2 promoted cell growth in leukemogenesis, and knockdown of IRF-2 blocked leukemia cell growth [20,21]. Elevated expression of IRF-2 was found in breast cancer, which was positively correlated to the tumor stage [22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…Also, IRF2 knock-down associated growth inhibition and induction of differentiation in a leukemia cell line further emphasizes the role of IRF2 deregulation in leukemogenesis. 37 Moreover, the receptor tyrosine kinase KIT, important for normal hematopoiesis, 38 was validated as a target of several NPM1 mut -associated miRNAs. KIT is crucial for maintaining HSC self-renewal and quiescence and was shown to be down-regulated in IRF2 deficient cells.…”
Section: Ccnd1mentioning
confidence: 99%